Educators as victims of workplace violence in selected secondary schools in the Capricorn District of the Limpopo Province, South Africa - Kgosimore, David Leepile (University of Limpopo, 2018)
Schools mirror the culture of violence that is endemic in our society. They have therefore become the focus of research on violence. However, much of our knowledge on violence that occurs in schools is on learners as victims of educator-on- learner and learner-on-learner violence; and as perpetrators of learner-on-learner because a great amount of research focuses only on these types of violence. Very little research has been done on teachers as victims of violence, and of learnerperpetrated violence, in particular. The little knowledge that is available indicates that objectionable behaviour, such as ill-discipline, class disruptions, and aggression and violent behaviour are aspects of interpersonal relationships that may cause teachers stress, burnout, job dissatisfaction, ill health, and lead to them quitting the teaching profession. This study investigated learner-perpetrated violence as a school and workplace violence. The results of this study, which are the outcomes of independently conducted qualitative and quantitative studies, confirm the parallel existence of learner-perpetrated violence and teacher stress and related ill health, behavioural reaction and organisational effects. The implications of these results are that the current legislation, the South African Schools Act, and regulations and policies associated with it, is inadequate in preventing the victimisation of teachers by learners, in their workplaces. Hence, this study recommends a model that can be implemented to prevent violence against teachers at a primary, secondary, and tertiary level. Learner violence is an occupational health and safety risk for teachers and needs to be handled in the same was as any other occupational health and safety hazard; hence the desire by teachers to be covered against violence at work under the Occupational Health and Safety Act. It is recommended that future research should focus on the incorporation of violence into the existing list of occupational hazard. This will force employers to take every step possible to prevent the victimisation of teachers in their workplaces. The reduction of incidents of violence against teachers has the potential of slowing teacher attrition down.
Thesis (Ph. D. (Criminology)) --University of Limpopo, 2018
Keywords: School violence; Victimization; Learner-on-learner violence; Violence in the workplace - Prevention; Violence in the workplace - Law and legislation